Nanoscale Insights into Photovoltaic Hysteresis in Triple‐Cation Mixed‐Halide Perovskite: Resolving the Role of Polarization and Ionic Migration. Issue 36 (19th July 2019) - Xia, Guozhan; Huang, Boyuan; Zhang, Ying; Zhao, Xingyu; Wang, Chen; Jia, Chunmei; Zhao, Jinjin; Chen, Weiqiu; Li, Jiangyu
Abstract: Triple‐cation mixed‐halide perovskites of composition Cs x (FA y MA1− y )1 −x Pb(I z Br1 −z )3 (CsFAMA) have been reported to possess excellent photovoltaic efficiency with minimal hysteresis; in this work, nanoscale insight is shed into the roles of illumination‐induced polarization and ionic migration in photovoltaic hysteresis. By examining the concurrent evolution of ionic distribution and spontaneous polarization of CsFAMA under light illumination using dynamic‐strain‐based scanning probe microscopy, strong linear piezoelectricity arising from photoenhanced polarization is observed, while ionic migration is found to be not significantly increased by lightening. Nanoscale photocurrents are mapped under a series of biases using conductive atomic force microscopy, revealing negligible difference between forward and backward scans, and local IV curves reconstructed from principal component analysis show minimal hysteresis of just 1%. These observations at the nanoscale are confirmed in a macroscopic perovskite solar cell made of CsFAMA, exhibiting a high efficiency of 20.11% and with hysteresis index as small as 3%. Ionic migration, polarization, and photocurrent hysteresis are thus directly correlated at the nanoscale, and photoenhanced polarization in triple‐cation mixed‐halide perovskites is established, which does not contribute to the photovoltaic hysteresis. Abstract : The nanoscale probing of concurrent ionic migration, spontaneous polarization, and photocurrent of triple‐cation mixed‐halide perovskites by dynamic‐strain‐based scanning probe microscopy reveals photoenhanced polarization that does not contribute to the photovoltaic hysteresis, supporting the concept that the primary mechanism responsible for photovoltaic hysteresis is ionic migration while polarization is harmless.